A Rationally Designed Thymidine‐Based Self‐Assembled Monolayer on a Gold Electrode for Electroanalytical Applications. Issue 7 (11th June 2015) - Datta, Dhrubajyoti; Bera, Raj Kumar; Jana, Saibal; Manna, Bhaskar; Roy, Debayan; Anoop, Anakuthil; Raj, C. Retna; Pathak, Tanmaya
Abstract A self‐assembled monolayer (SAM) of 1‐(3, 5‐epidithio‐2, 3, 5‐trideoxy‐β‐d‐threo‐pentofuranosyl)thymine (EFT) on a gold electrode was prepared and characterized by Raman spectral and electrochemical measurements. Voltammetric and electrochemical impedance measurements show that the SAM of EFT on a Au electrode impedes the electron‐transfer reaction. The SAM of EFT was successfully used for the voltammetric sensing of urate in neutral solution. The coexisting ascorbate anion does not interfere and therefore the EFT‐based electrode was able to quantify urate at the micromolar level in the presence of a large excess amount of ascorbate. To demonstrate the practical applications, the amount of urate in two different human serum samples was quantified by using the EFT‐based electrode; the results are in good agreement with those determined by the clinical method. DFT calculations show that both ascorbate and urate have noncovalent interactions including hydrogen‐bonding interactions with EFT.